Perindopril Reduces Arterial Pressure and Does Not Inhibit Exercise-Induced Angiogenesis in Spontaneously Hypertensive Rats - Miotto, Danyelle S. [UNESP]; Duchatsch, Francine [UNESP]; Macedo, Anderson G. [UNESP]; Ruiz, Thalles F. R. [UNESP]; Vicentini, Carlos A. [UNESP]; Amaral, Sandra L. [UNESP] (Lippincott Williams & Wilkins, 2021)
Sympathetic activity, arteriolar structure, and angiogenesis are important mechanisms modulating hypertension and this study aimed to analyze the effects of perindopril treatment, associated or not with exercise training, on the mechanisms that control blood pressure (BP) in hypertensive rats. Spontaneously hypertensive rats (SHR) were allocated into 4 groups: 1/sedentary (S); 2/perindopril (P, 3.0 mg/kg/d); 3/trained (T); and 4/trained + perindopril (TP). Wistar rats were used as normotensive sedentary control group. SHR were assigned to undergo a treadmill training (T) or were kept sedentary. Heart rate, BP, sympathetic activity to the vessels (LF-SBP), and skeletal muscle and myocardial morphometric analyses were performed. BP was significantly lower after all 3 strategies, compared with S and was accompanied by lower LF-SBP (-76%, -53%, and -44%, for P, T, and TP, respectively). Arteriolar vessel wall cross-sectional area was lower after treatments (-56%, -52%, and -56%, for P, T, and TP, respectively), and only TP presented higher arteriolar lumen area. Capillary rarefaction was present in soleus muscle and myocardium in S group and both trained groups presented higher vessel density, although perindopril attenuated this increase in soleus muscle. Although myocyte diameter was not different between groups, myocardial collagen deposition area, higher in S group, was lower after 3 strategies. In conclusion, we may suggest that perindopril could be an option for the hypertensive people who practice exercise and need a specific pharmacological treatment to reach a better BP control, mainly because training-induced angiogenesis is an important response to facilitate blood flow perfusion and oxygen uptake and perindopril did not attenuate this response.
Keywords: ACE inhibitors; physical training; hypertension